(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
The research identified the best fit model of personal resilience among 400 adolescents during a pandemic in Region XII, Philippines. A quantitative non-experimental method employing descriptive-correlation approach was utilized. The study applied mean, multiple regression, Pearson-product moment correlation, and structural equation modeling in analyzing the data. Results exhibited that the three exogenous variables, specifically, social support, self-efficacy, and spirituality, and the endogenous variable which is personal resilience were very high. The exogenous variables significantly influence the endogenous variable with spirituality as the best predictor of personal resilience. The best-fit model recognized the important connection of the three exogenous variables with personal resilience. The best fit model accentuated and established that social support, indicated by emotional support and instrumental support; self-efficacy, indicated by persistence; and spirituality, indicated by a feeling of security and mindfulness influenced and best predict the personal resilience of adolescents during a pandemic as indicated by novelty-seeking and emotional regulation. Nonetheless, social support, self-efficacy, and spirituality abetted adolescents to develop personal resilience to handle distress and cope during the pandemic.